Developmental Profile of Children with Autism Spectrum Disorder Versus Social Communication Disorder: A Pilot Study - Clara Dame; Marine Viellard; Sara-Nora Elissalde; Hugo Pergeline; Pauline Grandgeorge; Laure-Anne Garie; Federico Solla; Sonia De Martino; Elodie Avenel; Xavier Salle-Collemiche; Arnaud Fernandez; François Poinso; et al. (MDPI AG, 2024)
Background: Social Communication Disorder (SCD), introduced in the DSM-5, is distinguished from Autism Spectrum Disorder (ASD) by the absence of restricted and repetitive behaviors or interests (RRBIs). Aim: To compare the adaptive, sensory, communication, and cognitive profiles of children with ASD and SCD. Methods: The assessments of nine children with SCD and ten with ASD were compared with either Fisher's Exact Test or the Mann-Whitney Test. Assessments included the Vineland Adaptive Behavior Scales, the Autism Diagnostic Observation Schedule (ADOS), the Short Sensory Profile, Bishop's Children's Communication Checklist, a pragmatics evaluation, and the Wechsler Intelligence Scale for Children IV. Results: The total ADOS score and the second subtotal "Restricted and Repetitive Behaviors" were significantly higher (p = 0.022) in the ASD group than in the SCD group. The Vineland standard score for the "Socialization" domain was significantly lower (p = 0.037) in the ASD group (mean: 51 +/− 19) than in the SCD group (mean: 80 +/− 28). The working memory index score was also significantly lower (p = 0.013) in the ASD group compared to the SCD group. Conclusions: While ASD and SCD share similarities in communication and pragmatic difficulties, some distinctions have been identified, e.g. in executive functioning and the impact on socialization, which may be linked to the absence of RRBIs in SCD. These findings highlight the challenges posed by this nosographic separation during diagnostic evaluations due to the scarcity of discriminative tools.